Gastrointestinal Motility Variation and Implications for Plasma Level Variation: Oral Drug Products - Talattof, Arjang; Price, Judy C; Amidon, Gordon L (Molecular pharmaceutics, 2016)
The oral route of administration is still by far the most ubiquitous method of drug delivery. Development in this area still faces many challenges due to the complexity and inhomogeneity of the gastrointestinal environment. In particular, dosing unpredictably relative to motility phase means the gastrointestinal environment is a random variable within a defined range. Here, we present a mass balance analysis that captures this variation and highlights the effects of gastrointestinal motility, exploring what impacts it ultimately has on plasma levels and the relationship to bioequivalence for high solubility products with both high and low permeability (BCS I and III). Motility-dependent compartmental absorption and transit (MDCAT) mechanistic analysis is developed to describe the underlying fasted state cyclical motility and how the contents of the gastrointestinal tract are propelled.